Accountability, counter-terrorism and civil liberties - Blackbourn, J (Routledge, 2018)
When the Conservative-led Coalition government was elected in 2010, it was at a time when terrorism had started to decline, both domestically and on a global level. In the UK, only one person1 had been killed as a result of international terrorism since the 2005 London attacks. Globally, after a sharp rise in the mid-2000s, by 2008, the number of terrorist incidents and deaths caused by terrorism had begun to level out.3 And in 2009, the UK’s armed forces had withdrawn from military operations in Iraq. At the same time, the Coalition’s Programme for Government included a proposal to ‘reverse the substantial erosion of civil liberties and roll back state intrusion’. It was in these particular circumstances, that on entering office, the then Home Secretary, Theresa May initiated an internal review of the UK’s counter-terrorism and security powers. The purpose of the review was to ‘look at the issues of security and civil liberties in relation to the most sensitive and controversial counter-terrorism and security powers and, consistent with protecting the public and where possible, to provide a correction in favour of liberty.’ The review did indeed lead to the repeal of some of those controversial powers, including control orders,6 stop and search, and the 28 day period of extended pre-charge detention for terrorist suspects.8 The extent to which it actually provided a correction in favour of liberty is somewhat less clear. Control Orders were repealed, but immediately replaced with the only slightly less stringent TPIMs – Terrorism Prevention and Investigation Measures. The controversial stop and search powers in section 44 of the Terrorism Act 2000 were repealed, but only after the European Court of Human Rights found that they breached the right to respect for private life in Article 8 of the European Convention on Human Rights (ECHR). The maximum period of extended pre-charge detention was reduced from 28 days to 14, albeit the government also laid a Draft Detention of Terrorist Suspects (Temporary Extension) Bill before Parliament, the effect of which would be to extend the maximum period of pre-charge detention from 14 to 28 days in an emergency.